Design and Development of Captopril Gastro-Retentive Tablet Using Natural Polymers of Maize and Jowar Plant: Pharmaceutical Science-Pharmaceutics - P. Gayakwad, Bhushan; R. Bavaskar, Sunil; Fulzele, Sandip; Yadav, Reenu; Gauttam, Vinod; Sawale, Jyotiram (International Journal of Life Science and Pharma Research, 2023)
Nowadays, the use of natural polymers as an alternative to synthetic gastro-retentive polymers is increasing. Such natural raw materials are highly biocompatible and biodegradable with no or significantly fewer side effects and are economical too. The main aim of this research work was to design a gastro-retentive tablet of Captopril by using Maize Stem Pith (MSP) powder and Jowar Stem Pith (JSP) as novel natural low-density polymers and also to sustain the drug release for up to 12 hours. Our objective behind this research is to prepare the gastro-retentive tablet, evaluate it for floating behavior, and to achieve the sustained release effect for at least 12 hours. The novelty of this research work is that MSP powder and JSP powder possesses low density. Thus, gastro-retentive tablets with a low-density (floating) approach can be prepared at a very lost cost compared to the currently marketed formulation. Gastro-retentive tablets of Captopril were designed by using MSP and JSP powder. Using design-expert® version 13, the formulations were prepared using a 32-complete factorial design. The gastro-retentive tablet showed good floating behavior and dissolution pattern, which sustains the release of the drug for up to 12 hours. The optimization study using a contour plot and response surface plot suggested that formulation R9 is an optimized batch among all batches. The current research indicated that there is an increase in floating time with a corresponding decline in the dissolution rate of the tablet as the concentration of MSP powder and JSP powder increases. The optimized formulation R9 consists of MSP powder and JSP powder at 12% and 8 %, respectively, in combination with HPMC (K-100M), and has proven excellent floating behavior and expected drug release pattern. Therefore, MSP powder and JSP powder could be used as suitable low-density novel polymers to design gastro-retentive tablets of Captopril.